Outcomes of Drug Inventory Development in Primary Health Care Units of Maharaj Nakhon Si Thammarat Hospital Network - ว่องทวีเจริญพร, ธิดารัตน์ (Journal of Health Science of Thailand, 2023)
The objective of this study was to investigate the outcomes of drug inventory development in primary health care units of Maharaj Nakhon Si Thammarat Hospital Network using drug system module, to reduce the items and cost of inventory associated with drugs expiring within 6 months, to reduce the items and cost of inventory of expired drugs after intervention, and to assess the saved cost of inventory when the inventory rate was set to 1.5 months. It was conducted as a quasi-experimental research with one group pre-test - post-test design. The samples were 18 primary health care units of Maharaj Nakhon Si Thammarat Hospital Network with a standardized structure. The data were collected during 6 January to 31 August 2020. Data collection tools were general information questionnaires and assessment form corresponding to quality standard criteria of the drugs inventory in the drug system module of Nakhon Si Thammarat Province, complying with the evaluation criteria for the star-rating of Sub-district Health Promoting Hospital 2020. The data were analyzed by using descriptive statistics and inferential statistics (paired t-test). It was found that, the mean score after intervention was more than that before intervention with statistical significance [4.67±2.68 (20.11%) and 16.06±3.08 (76.19%), p<0.001]. Before the intervention, the items of drugs to be expired within 6 months were 91 with the cost of 52,116 baht. The items and cost of inventory of expired drugs before and after intervention were 51 items with cost of 29,444 baht and 3 items with cost of 1,544 baht, respectively. The cost saved by the inventory with the inventory rate of 1.5 months was 302,790 baht.